Ekspansywność - nowy wskaźnik oceny regionalnego rozwoju gospodarczego - Niklewicz-Pijaczyńska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The aim of the article is to show the essence and meaning expansiveness has for regional economic development. Starting from functioning in practice, indicators of innovativeness and creativity it also describes attempts to build a new indicator based on expansiveness. The article presents selected aspects of expansiveness on the basis of data on the situation of the Lower Silesia region
Keywords: ekspansywność; innowacyjność; kreatywność; regionalny rozwój gospodarczy; region; Dolny Śląsk